Customers perception of integrity initiatives in University Technology MARA : A case study of University Technology MARA Sarawak / Hajah Oriah Haji Akir ... [et al.] - Haji Akir, Hajah Oriah; Malie, Senian; Omar, Noraida (Universiti Teknologi MARA Cawangan Sarawak , Kampus Samarahan, 2011)
Integrity is one of the most important personal qualities that any individual in a position of power or responsibility must possess, be it in business or politic, public or private life. Thus integrity has become a genuine area of concern in the civil service of many countries around the world. In view of the concern for integrity issues, the main aims of this study are: a) to determine the perception of customers regarding the integrity initiatives of UiTM Sarawak); b) to identify the perception of vendors and/or suppliers regarding the integrity initiatives of UiTM Sarawak; c) to examine the relationship between integrity dimensions of prevention, accountability, enforcement and job conduct. In this study, the framework was also developed to establish the relationship between integrity dimensions and the employees’ job conduct based on the work of Ashour (2004).